Experimental Implementation of a Pulse Compression Technique Using Coherent Plane-Wave Compounding - Benane, Yanis Mehdi; Bujoreanu, Denis; Lavarello, Roberto J.; Varray, Francois; Escoffre, Jean-Michel; Novell, Anthony; Cachard, Christian; Basset, Olivier (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2018)
The axial resolution of an ultrasound imaging system is inversely proportional to the bandwidth of the emitted signal. When conventional pulsing (CP) is used, the impulse response of the transducer and the excitation signal determine together the shape of the emitted pulse and its bandwidth. A way to increase the ultrasound image resolution is to increase the transducer's limited passband. The resolution enhancement compression (REC) is a coding technique that boosts the signal energy in the transition frequency bands, where the energy transduction of the ultrasound probe is less efficient. Consequently, image quality metrics including axial resolution, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) can be improved. In this paper, the objective is to combine REC with coherent plane-wave compounding (CPWC) in order to achieve better image quality at an ultrafast acquisition rate. Promising results are obtained from both wire and cyst phantoms using an excitation signal designed to provide a 54% increase in bandwidth over the one obtained with a broadband pulse excitation at -6 dB. The experimental bandwidth measured from the backscattered echoes was improved by 49% for the wire phantom, when using the CPWC-REC technique compared to CPWC-CP. Furthermore, the axial resolution as derived from the modulation transfer function of the envelope of the wire target was enhanced by 29%. The CNR and SNR were improved up to 9 and up to 4 dB, respectively, in the cyst phantom. These results reveal that CPWC-REC is able to achieve higher spatial resolution, compared to CPWC-CP, with better SNR and CNR. Moreover, experimental results show that an effective implementation on a research scanner of REC using plane-wave imaging is possible. Consistent in vivo acquisition results on rabbit are presented and discussed.